Improving Listening Skills In Children Through Storytelling Using A Flanel Board At Alhariri, Tebo Ulu District: Meningkatkan Kemampuan Menyimak Anak Melalui Metode Bercerita Menggunakan Papan Flanel di Raudatul Athfal Alhariri Kecamatan Tebo Ulu - Widia Fitri; Mahluddin Mahluddin; Achmad Fadlan (The Future of Education Journal, 2026)
This study aimed to determine whether the storytelling method using a flannel board could improve the listening skills of children at RA Al Hariri. The data collection techniques used in this study were observation, interviews, and documentation as supporting instruments. This research was conducted as a Classroom Action Research consisting of three cycles.The results of the study showed a significant improvement in children’s listening skills in each cycle. In Cycle I, Meeting 1, there were 4 children (40%) categorized as undeveloped, while 6 children (60%) were categorized as beginning to develop. In Cycle I, Meeting 2, 4 children (40%) were categorized as beginning to develop, while 6 children (60%) developed as expected. In Cycle II, Meeting 1, there were 3 children (30%) categorized as beginning to develop and 7 children (70%) developed as expected. Furthermore, in Cycle II, Meeting 2, 5 children (50%) developed as expected and 5 children (50%) developed very well. In Cycle III, Meeting 1, there were 3 children (30%) categorized as developing as expected, while 7 children (70%) developed very well. Finally, in Cycle III, Meeting 2, all 10 children (100%) were categorized as developing very well.